The racialization of school failure in brazilian basic education: bibliographic review (2010-2020) (Research, Society and Development, 2022)
This article deals with a literature review on school failure adopting two methodological directions: firstly, a review of the historical landmarks of academic research on school failure was carried out, analyzing previously established categories, namely: a) theoretical and epistemic conceptions in the concerning the theoretical-methodological basis of the works; b) their epistemological and explanatory relationships about the phenomenon studied from ethnic-racial issues; c) who were the subjects questioned in the works regarding the objects of study in question and their methodological design; and d) analyze the educational context researched in the works. Then, the current research on this topic was analyzed, intersected with the school complaint in basic education, with the objective of analyzing the content (words) referring to the titles and abstracts of these studies, focusing on a problematization anchored in content analysis. As a result of this work, the perception about the role of School Psychology in this field of studies is presented, as well as the erasure of ethnic-racial variables regarding the analyzes and problematizations that deal with school failure in Brazilian basic education.